Makna Ketaatan bagi Para Calon Imam Diosesan dalam Terang Injil Yohanes 8: 32-33 - Mango, Hendrikus; Rau, Beatus Celvinsantius Riwu (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The calling to be the ministers of Word and Sacrament is considered God’grace granted upon His people of God who are faithful and willing follow His path. This sacred calling of priesthood undergoes in a long-tiring process started from basic to higher formation (read education) when the candidates take their philosophical and theological studies, and finally they are ordained priests for the services of God’s people. The Interdiocesan Seminary of Saint Peter, Ritapiret in Flore, Indonesia is an educational body for the candidates of the local priests under the local Church of Maumee diocese, where in the candidates grow and mature in many aspects, including intelectual, spiritual, missionary and human characteristics which are centered in the loving service characteristics that have been lived out by the High Priest, Jesus the Lord. ‘The meaning of obedience for the the Diocese priestly candidates in the light of John 8: 32-33’ aims at searching and tracing the divine values treasured in the Gospel of John 8: 32-33, on which the writer will base the whole juxtaposition on the matter of the spirit of obedience which are comprehended and lived out by the Interdiocesan seminarians – the candidates of the local Church priests.